PRODUCTION OF Y AND USY ZEOLITE FOR THE ACTIVE COMPONENT OF CRACKING CATALYST - Subagjo, Subagjo (Jurnal Zeolit Indonesia, 2008)
Standard Y zeolite has been prepared from sodium aluminate as an alumina source and Cab-O-Sil or sodium silicate as a silicate source. This study in particular aimed to obtain a reliable procedure to produce Y zeolite with Si/Al ratio â¥5. The resulted zeolite was then converted into Ultra Stable Y Zeolite (USY) through hydrothermal dealumination at high temperature. The study managed to procure a formulae and procedure to produce a zeolite Y which has SiO2/Al2O3 > 5 and a very stable USY. The procedure succeeded in obtaining synthesized USY that is ready to use as an active phase of cracking catalyst by combining it with other components which are matrix (modified clay and active matrix) and additives (ZSM- 5).